FENOMENA PEMBERIAN MAHAR UNIK PADA MASYARAKAT MUSLIM SASAK DI TINJAU DARI PLURALISME HUKUM - Yusuf, Muhammad Affandi (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
This research is motivated by the unique phenomenon of giving dowry to the Sasak Muslim community, namely in the form of dowry giving grilled chicken, sandels, shrouds, google endsense. Looking at the phenomenon that occurs, it is necessary to look at the concept of giving dowry in Islamic law, and customary law, and then how the legitimacy of giving a unique dowry in Islamic law and customary law is justified. This research is a type of library research (literature study) which is qualitative in nature with a normative-empirical approach. The arguments presented in this study use legal pluralism analysis. Legal pluralism, according to MB Hooker, is a situation characterized by the coexistence of two or more legal systems that interact with each other in the process of legal modernization in a country. Legal pluralism is neutral in nature, meaning that in its interaction there are no forces that dominate each other or are superior to the other. In the case of giving unique dowry, it can be seen that there are no laws that dominate each other, but what is a factor in the legitimacy of the unique dowry is the willingness of women to receive the dowry in accordance with Islamic law or customary law that applies to the Sasak tribal community.